Glutathione for skin lightning: A regnant myth or evidence-based verity - Sidharth Sonthalia; Abhijeet Kumar Jha; Aimilios Lallas; Geraldine Jain; Deepak Jhakar (Mattioli1885, 2018)
The recent hype surrounding the antimelanogenic properties of glutathione has resulted in physicians frequently administering it as a "wonder" drug for skin lightening and treatment of hyperpigmentation, especially in ethnic populations with darker skin tones. This phenomenon has seen a recent surge owing to aggressive marketing and capitalization of pharma-cosmeceutical companies. However, the unbridled and prodigal use of it, especially as a parenteral formulation, seems unjustified, given the lacunae in our knowledge about its antimelanogenic potential, limited clinical evidence favoring its role in skin lightening, and the statutory ban/advisory issued by certain federal agencies. Even though parenteral glutathione is approved only for severe liver disorders and for prevention of chemotherapy associated neurotoxicity, the lack of statutory laws governing the use of systemic glutathione in most countries has contributed to its unchecked use for skin lightening. The current clinical evidence of intravenous glutathione for skin lightening is limited to a single study with a dubious study design and apparently flawed analysis of results, casting doubt on the drug's efficacy and reported adverse effects. Two studies evaluating oral/sublingual administration and one trial involving the use of topical glutathione reported good safety profile and appreciable but reversible results on skin tone. In this article, we shall review and discuss the current status of glutathione as a skin lightening agent and address the sundry unanswered queries regarding the dosage, duration of use and longevity of accrued effects based on clinical evidence and recent insights into its antimelanogenic mechanism.